2008
DOI: 10.1016/j.chemosphere.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal accumulation in Halimione portulacoides: Intra- and extra-cellular metal binding sites

Abstract: Salt marsh plants can sequestrate and inherently tolerate high metal concentrations found in salt marsh sediments. This work intended to understand the Halimione portulacoides (L.) Aellen strategies to prevent metal toxicity, by investigating the metal location in different plant organs and in the cell. A sequential extraction was performed on leaves, stems and roots of H. portulacoides in order to determine and compare the metal (Zn, Pb, Co, Cd, Ni and Cu) concentration in several fractions of the plant mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 42 publications
4
51
0
3
Order By: Relevance
“…This was also shown by the low translocation factor in all the investigated plant species. Sousa et al [7] reported that the translocation factor in Halimione portulacoides was lower than 1, which this study confirms. The high mobility of Ni and Zn [7,15] may explain the highest translocation factors observed for these metals when considering the allocation of metals from the root to the leaves and from the root to the stems.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This was also shown by the low translocation factor in all the investigated plant species. Sousa et al [7] reported that the translocation factor in Halimione portulacoides was lower than 1, which this study confirms. The high mobility of Ni and Zn [7,15] may explain the highest translocation factors observed for these metals when considering the allocation of metals from the root to the leaves and from the root to the stems.…”
Section: Discussionsupporting
confidence: 84%
“…The same kind of distribution was reported for Zn, Cu, Ni and Co in Halimione portulacoides from the Tagus estuary by Sousa et al [7]. Populations of Suaeda maritima from the inland saline areas preferred accumulation of metals in the above-ground parts (stems and leaves), while populations of the same species from the maritime saline areas preferred accumulation in the root.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results show that more than 93% of the total mer cury found in the roots was immo bi lized in the cell walls and 72% of the total mer cury found in the leaves were in the also in the cell walls. Sousa et al (2008) found that in the pres ence of other met als (Zn, Pb, Co, Cd, Ni and Cu) simi lar results were obtained, with met als being mostly retained in the cell wall com part ments. Accord ing to Zor noza et al (2002), a higher accu mu la tion of met als in cell walls can func tion as a pro tec tion bar rier by reduc ing the metal con cen tra tion in the cyto plasm.…”
Section: Discussionmentioning
confidence: 86%
“…Moreno et al, 2013;Cambrollé et al, 2012a;Cambrollé et al, 2012b;Sousa et al, 2008). Esta gran tolerancia se debe a los eficientes mecanismos de detoxificación y compartimentalización que presenta esta especie; los metales están principalmente asociados a la pared celular de las células vegetales, lo que actúa de barrera contra los efectos nocivos de los metales al mantenerlos alejados del citoplasma y otros orgánulos intracelulares con actividad metabólica (Sousa et al, 2008).…”
Section: Bustarviejounclassified